Medico-legal Aspects in Dentistry - Smita R. Priyadarshini1, Pradyumna Ku Sahoo2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dentists as healthcare professionals have a duty and standard for patient care. Any violation in the duty andpractice makes dentists liable to negligence & legal actions. Law protects the dentists as well as ensuresethical practice. With the steady increase in the number of dental graduates and decrease number of jobfacilities,the dental profession seems to descend of its ethical standards. So a thorough knowledge about themedico-legal aspects is mandatory for smooth execution & delivery of productive services. In this paper wereview comprehensively different aspects of avoiding negligence.